Participation in a pre-registration student interprofessional education (IPE) society: influence on subsequent professional practice - Hirsch, Christine; Audet, Emily; Dawood, Ekrahh; Beardmore, Freya; Hussain, Nafeesa; Wong, Wing Chi; Barry, Robert J.; Buckley, Sharon (Frontiers in Medicine, 2025)
BackgroundStudent interprofessional education (IPE) societies or organizations are popular ways to support pre-registration health professions students to develop the understanding and skills needed for collaborative working. Our experience with the University of Birmingham Knowledge and Skills Exchange (KASE) is that, whilst such societies can be excellent vehicles for IPE, sustaining them can be challenging; and that consistent faculty support, adequate resource and a focus for society activities are needed for them to flourish. Whilst the longer term impact of pre-registration IPE has been demonstrated, less is known about the influence of student IPE society membership on participants’ subsequent professional practice. To inform institutional decisions about establishing and maintaining a student IPE society, we have investigated the perceptions of early career health professionals who were KASE members during their pre-registration training.MethodsKASE alumni working as early career health professionals were invited to participate in the study. Their perceptions of the influence of KASE on their transition to practice and experience as early career health professionals were explored through online semi-structured interviews and interview transcripts analyzed thematically. Resulting themes were reviewed for relevance to the University of Birmingham (UK) IPE Framework, which uses the competency domains of the Canadian Interprofessional Health Collaborative Competency Framework as the required learning outcomes for IPE at Birmingham.ResultsEight interviews with former KASE members were conducted between November 2022 and March 2023. Interviewees had between 2 and 5 years of experience in their professional role. Six themes relating to the influence of KASE on their subsequent professional practice were identified: interprofessional communication, teamworking, patient-centered care, leadership and organizational skills, confidence and resilience. Three of these themes related to required IPE learning outcomes. Two further themes: time to build relationships; and informality and autonomy, suggested possible reasons for such influence.ConclusionEarly career health professionals considered that participation in the KASE student IPE society helped their transition into the healthcare work environment and encouraged them to adopt a more collaborative and patient-centered approach. Benefits reported suggest that faculty support for institutional student IPE societies is worthy of consideration.